Endosome-ER Contacts Control Actin Nucleation and Retromer Function through VAP-Dependent Regulation of PI4P - Dong, Rui (2016)
VAP (VAPA and VAPB) is an evolutionarily conserved endoplasmic reticulum (ER)-anchored protein that helps generate tethers between the ER and other membranes through which lipids are exchanged across adjacent bilayers. Here, we report that by regulating PI4P levels on endosomes, VAP affects WASH-dependent actin nucleation on these organelles and the function of the retromer, a protein coat responsible for endosome-to-Golgi traffic. VAP is recruited to retromer budding sites on endosomes via an interaction with the retromer SNX2 subunit. Cells lacking VAP accumulate high levels of PI4P, actin comets, and trans-Golgi proteins on endosomes. Such defects are mimicked by downregulation of OSBP, a VAP interactor and PI4P transporter that participates in VAP-dependent ER-endosomes tethers. These results reveal a role of PI4P in retromer-/WASH-dependent budding from endosomes. Collectively, our data show how the ER can control budding dynamics and association with the cytoskeleton of another membrane by direct contacts leading to bilayer lipid modifications.